1996
DOI: 10.1207/s15328023top2302_1
|View full text |Cite
|
Sign up to set email alerts
|

An Active-Learning Approach to Teaching the Undergraduate Psychology and Law Course

Abstract: This article describes an active-learning approach to teaching an undergraduate psychology and law course specifically designed to improve critical-thinking skills. After reviewing the concepts of active learning and critical thinking, we describe the course and present data and observations regarding its success. Finally, we discuss strategies for handling problems that may arise when teaching a psychology and law course using this approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 12 publications
2
47
0
Order By: Relevance
“…The pictures and scenarios the students provided to exemplify their chosen topics provided a way for students to remember the information. These results are consistent with established scholarly literature that indicate the arts and innovative activities strengthen the students' learning [10,11,24,[32][33][34].…”
Section: Discussionsupporting
confidence: 90%
“…The pictures and scenarios the students provided to exemplify their chosen topics provided a way for students to remember the information. These results are consistent with established scholarly literature that indicate the arts and innovative activities strengthen the students' learning [10,11,24,[32][33][34].…”
Section: Discussionsupporting
confidence: 90%
“…Much educational research demonstrates that the very nature of the lecture approach does not promote student learning (e.g., see Bonwell and Sutherland 1996;Browne et al 1991;Curry and Makoul 1996;Lawson 1995;Misale et al 1996;Nance and Nance 1990;Perry et al 1996;Poppenhagen et al 1982;Watson et al 1996). For example, confusion and boredom may occur 10-20 minutes into lectures, students remember more information from the first 10 minutes of class than from the last 10 minutes, and students recall significantly more information immediately following a lecture than one week later (McKeachie 1986).…”
Section: Weaknesses Of Lecturing: Why Active Learning Is Necessarymentioning
confidence: 99%
“…More importantly, student retention of knowledge and student performance declines significantly after this period (Bonwell and Sutherland 1996;Misale et al 1996;Nance and Nance 1990;Poppenhagen et al 1982). Active learning strategies increase student retention of knowledge, and student attention and interest (Bonwell and Sutherland 1996;Curry and Makoul 1996;Perry et al 1996;Watson et al 1986). At the same time, strategies which actively engage students make class more fun (Lawson 1995).…”
mentioning
confidence: 99%
“…Previous research has demonstrated the beneficial effects of active study on learning outcomes (e.g. Burbach et al, 2004;Hake, 1998;Laws, Sokoloff, & Thornton, 1999;Perry et al, 1996;Redish, Saul, & Steinberg, 1997). In addition, all three strategies examined in Experiment 3 can be usefully employed to actively study and assimilate text-based arguments (Butchart et al, 2009;Kintsch & van Dijk, 1978;Taylor, 1982;Taylor & Beach, 1984).…”
Section: Methodsmentioning
confidence: 77%
“…The importance of this active construction of arguments is also relevant given recent research findings regarding the beneficial effects on learning outcomes of infusing active learning into classroom settings (e.g. Burbach, Matkin, & Fritz, 2004;Butchart et al, 2009;Perry, Huss, McAuliff, & Galas, 1996). As AM software is designed specifically for active construction of arguments, a logical progression in AM research is to assess whether active learning conducted through AM construction enhances memory performance.…”
Section: Discussion Of Experimentsmentioning
confidence: 99%